Identifying effects of land use cover changes and climate change on terrestrial ecosystems and carbon stocks in Mexico. (November 2018) - Mendoza-Ponce, Alma; Corona-Núñez, Rogelio; Kraxner, Florian; Leduc, Sylvain; Patrizio, Piera
Highlights: From 1993–2007, most of deforestation was in tropical dry forests and scrublands. Expansion of rain-fed agriculture and pasture explained 45 and 41% of deforestation. Pastures are widespread in tropical evergreen and temperate forests. Anthropogenic covers could increase from 26% of the country, in 2011 to 37% by 2050. Mexico can be responsible for 1–2% of LUCC global emissions. Abstract: Land use cover change (LUCC) has a crucial role in global environmental change, impacting both ecosystem services and biodiversity. Evaluating the trends and possible alternatives of LUCC allows quantification and identification of the hotspots of change. Therefore, this study aims to answer what the most vulnerable ecosystems and the carbon stocks losses to LUCC are under two socioeconomic and climate change (CC) scenarios–Business as Usual (BAU) and Green. The scenarios integrate the Representative Concentration Pathways, and the Shared Socioeconomic Pathways, with a spatially explicit LUCC. Distance to roads and human settlements are the most explicative direct drivers of LUCC. The projections include thirteen categories of natural and anthropogenic covers at a fine resolution for Mexico for the two scenarios. The results show that 83% of deforestation in the country has taken place in tropical dry forests, scrublands, temperate forests, and tropical evergreen forests. Considering the range of distribution of natural vegetation and the impacts of LUCC and CC, tropical dry and evergreen forests, followed by other vegetation and cloud forests are shown to be most vulnerable. By 2011, anthropogenic covers accounted for 26% of the country's cover, and by 2050, according to the BAU scenario, they could account for 37%. The Green scenario suggests a feasible reduction to 21%. In 1985, Mexico had 2.13 PgC in aboveground biomass, but the LUCC would be responsible for 1–2% of LUCC global emissions, and by 2100, it may account for up to 5%. However, if deforestation were reduced and regeneration increased (Green scenario), carbon stocks would reach 2.14 PgC before 2050. Therefore, identifying which natural covers are the most vulnerable to LUCC and CC, and characterizing the principal drivers of ecosystems loss are crucial to prioritizing areas for implementing actions addressing resources to combat the loss of ecosystems and carbon stocks.